Interaksi Obat Pada Pasien Geriatri: Kajian Berbasis Evidence Tentang Kombinasi Antihipertensi dan Obat Non Steroidal Anti-Inflammatory - Alya, Rahma; Khuriyah, Khuriyah; Ananda, Meisya Dwi; Putra, Hasan Etanov; Adzkia, Muhammad Adit; Putri, Mukarromah Dita; Hilmi, Indah Laily (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
The number of elderly individuals continues to increase globally, accompanied by a high prevalence of chronic diseases, particularly hypertension and musculoskeletal disorders. This condition makes geriatric patients vulnerable to polypharmacy, which increases the risk of drug interactions, one of which is between antihypertensives and non-steroidal anti-inflammatory drugs (NSAIDs). Such interactions can potentially reduce therapy effectiveness, cause electrolyte disturbances, and lead to acute kidney injury (AKI). This study aims to comprehensively examine the interaction between antihypertensives and NSAIDs in geriatric patients and its impact on therapy safety. The method used is a literature review by selecting national and international articles published between 2015 and 2025, written in either Indonesian or English, specifically investigating interactions between antihypertensives (β-blockers, ACE inhibitors, ARBs, diuretics, and CCBs) and NSAIDs. The review results indicate that most interactions are pharmacodynamic, involving either antagonism or negative synergism. NSAIDs can reduce the effectiveness of antihypertensive therapy through mechanisms such as sodium retention, afferent arteriolar vasoconstriction, and decreased renal perfusion. In certain combinations, such as the triple whammy phenomenon (NSAIDs, diuretics, and RAAS inhibitors), the risk of AKI and hyperkalemia increases significantly. This risk is higher in geriatric patients with decreased kidney function, comorbidities, and concurrent use of multiple drugs. In conclusion, the interaction between antihypertensives and NSAIDs in the elderly population is an important clinical issue. Therefore, close monitoring of kidney function and electrolytes, using the lowest effective dose for the shortest possible duration, and patient education to avoid self-medication are necessary to ensure therapy safety.